2018
DOI: 10.1039/c8ay01101j
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of estrogens in infant formulas by isotope dilution liquid chromatography-tandem mass spectrometry

Abstract: Isotope dilution liquid chromatography-tandem mass spectrometry without any derivatization step was developed to screen estrogens in real infant formula samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Infant foods are wildly concerned for its potential safety issues [5,6]. It is reported that PAH levels are highest in fatenriched foods, including infant formula powder, that contain vegetable oils such as coconut oil, palm oil, and soybean oil [4,[7][8][9]; the oils have been reported to contain PAH contamination to varying degrees in the order of corn oil, grape seed oil, groundnut oil, olive oil, palm oil, pumpkin seed oil, rapeseed oil, rice bran oil, soybean oil, and sunflower seed oil [10][11][12][13]; the PAHs enter infant formula powders through these vegetable oils.…”
Section: Introductionmentioning
confidence: 99%
“…Infant foods are wildly concerned for its potential safety issues [5,6]. It is reported that PAH levels are highest in fatenriched foods, including infant formula powder, that contain vegetable oils such as coconut oil, palm oil, and soybean oil [4,[7][8][9]; the oils have been reported to contain PAH contamination to varying degrees in the order of corn oil, grape seed oil, groundnut oil, olive oil, palm oil, pumpkin seed oil, rapeseed oil, rice bran oil, soybean oil, and sunflower seed oil [10][11][12][13]; the PAHs enter infant formula powders through these vegetable oils.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the LC-IDMS/MS method, u A is the uncertainty originating from the repeatability of LC-IDMS/MS measurement, and u B is the uncertainty stemming from the pure AFB 1 CRM ( P std ), preparation of the calibration solution, and weighing of the sample ( m s , m IS ). However, as for the SA LC-FLD method, u A is the uncertainty originating from the repeatability of the SA LC-FLD measurement and u B is the uncertainty from the calibration curve, pure AFB 1 CRM ( P std ), and weighing of the sample ( m s ) . Additionally, the two methods have been regarded as equal precision.…”
Section: Resultsmentioning
confidence: 99%
“…However, as for the SA LC-FLD method, u A is the uncertainty originating from the repeatability of the SA LC-FLD measurement and u B is the uncertainty from the calibration curve, pure AFB 1 CRM (P std ), and weighing of the sample (m s ). 39 Additionally, the two methods have been regarded as equal precision. Thus, the standard uncertainty of value is characterized using the following equation (eq 14)…”
Section: Stability Monitoringmentioning
confidence: 99%